Lithotype-based modelling and simulations of coal degradation conditioned by both high and low energy breakage. (15th November 2018) - Shi, Fengnian; Liu, Hongping; Rodrigues, Sandra; Esterle, Joan; Nguyen, Anh K.; Manlapig, Emmanuel
Highlights: Lithotype-based modelling of coal degradation and fines generation is presented. Covering both high energy single impact and low energy repetitive breakage. The JK size-dependent breakage model used for characterisation, modelling and simulation. Coal lithotype has a significant effect on coal degradation and fines generation. Abstract: The control of coal fragmentation and fines generation during mining and processing is important in coal production. A method to characterise, model and simulate coal size degradation and fines generation based on lithotypes has been developed. This method was refined to cover both high energy single impact to mimic blasting and crushing and low energy incremental breakage to mimic coal handling, transiting, stockpiling and processing. The JKRBT was utilised to characterise high energy single impact breakage and drop shatter tests were used to characterise low energy incremental breakage. X-ray Computed Tomography (XCT) scanning was used as an undisruptive technique to estimate size distributions of drill cores in the drop shatter tests. The JK size-dependent breakage model was applied for breakage characterisation, size degradation modelling and fines generation simulation. The results indicate that coal lithotype has a significant influence on coal degradation and fines generation. This paper has demonstrated that the adaption of two distinct breakage characterisation tests and linkage via the one model is a significant advance in quantifying coal degradation and fines generation during coal production.